Attitude Of Border Communities Towards Local Wisdom: Between Modernization And Preservation - Nurhadianto, Nurhadianto; Hana Mauludea (Sean Institute, 2024)
This research aims to analyze and explain the understanding, feelings and actions of border area communities regarding the local wisdom values of Antar Pakatan in Simpang Empat Village, Sambas Regency. This research method uses naturalistic qualitative research methods. Data techniques and analysis use observation and interviews. The results of the research show that the attitude of border communities towards the value of local wisdom in Simpang Empat Village, Sambas Regency can be categorized as a high spirit of mutual cooperation and solidarity. The attitude of the Sambas community in maintaining local wisdom shows their awareness of the importance of preserving cultural heritage and traditional knowledge which has become an integral part of their identity.